From chaos to restoration : an integrative reading of Isaiah 24-27 - Johnson, Dan G. (Journal for the study of the Old Testament. Supplement series ;, 1988)
This work takes seriously the compositional nature of Isaiah 24-27 and moves beyond the schema established by Bernard Duhm who defined these chapters as a composite of unrelated pericopae. This new approach has enabled new light to be brought to such perennial problems as the identity of the city (or cities), the date of the composition, the structure of the four chapters, the perspective of the composition and the nature of the resurrection alluded to in 26.19. This study concludes that Isaiah 24-27 was written during the exile, a time significantly earlier than is commonly held by critical s.